MINERAL NUTRITION AS A FACTOR OF INCREASING PHOTOSYNTHETIC PRODUCTIVITY AND YIELD OF FIELD PEA - Yeremko, L. S.; Hanhur, V. V.; Кyrychok О. О.; Sokyrko, D. P. (Scientific Progress & Innovations, 2019)
Grain legume crops, field pea (Pisum sativum L.) in particular, combine two major physiological processes – photosynthesis and symbiotic nitrogen fixation. Due to this, they not only satisfy their own nitrogen requirements, but also increase soil fertility and improve the ecological status of agro-phytocenoses. These crops have a unique chemical composition, combining high protein content with high amounts of fat and carbohydrates. Due to their peculiarities, they occupy a prominent place among the crops of world arable farming. Therefore, it is urgent to develop technological measures to control the processes of forming the productive potential of field pea. The purpose of the research was to find out the effect of seed inoculation with microbiological preparation, different levels of mineral fertilizers’ application on the formation of photosynthesis active surface, its productivity and yield of pea grain. The following scientific methods were used in the research: analysis, synthesis, field, and statistical. The results of the conducted studies show that the optimization of plant nutrition due to different levels of mineral fertilization, as well as biological nitrogen and seed inoculation with Rizogumin microbiological preparation contributed to improving the conditions of the assimilation apparatus formation, in particular to increasing the area of the crops’ leaf surface by 0.4−2.6 thousand m²/ha or 1.5–8.4 %. It was found that the net productivity of photosynthesis, on average during the pea cultivation season, varied from 4.07 to 6.76 g/m² per day on different backgrounds of mineral fertilizers’ application, increasing with the improvement of the plant supply of with mineral nutrients. It also contributed to the prolongation of the period of the leaf surface in the photosynthesis active state, which was evidenced by increasing the values of photosynthetic potential from 1.03 to 1.41 thousand m²/ha. It was determined that the yield of pea grain as a result of using mineral fertilizers increased by 0.23−0.51 t/ha or by 7.9−17.6 %, seed inoculation by 0.15 t/ha or 5.2 %, the combination of seed inoculation and mineral fertilization − by 0.29−0.62 t/ha or 9.5−20.3%. The experiment also demonstrated the increase of crop yields at transferring part of nitrogen from the basic application to additional fertilization, both together with pre-sowing treatment of seeds with Rizogumin microbiological preparation and without it.